Sighting of Jerdon’s Baza Aviceda jerdoni (Blyth, 1842) from Great Nicobar Island, Andaman & Nicobar archipelago, India - Sivaperuman, C.; Gokulakrishnan, G. (Journal of the Bombay Natural History Society (JBNHS), 2016)
No Abstract.